2022
DOI: 10.1021/acsomega.2c02083
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of α-Fe2O3 Nanostructures: Synthesis, Characterization, and Their Promising Application in the Treatment of Carcinoma A549 Lung Cancer Cells

Abstract: In the present work, iron nanoparticles were synthesized in the α-Fe 2 O 3 phase with the reduction of potassium hexachloroferrate(III) by using l -ascorbic acid as a reducing agent in the presence of an amphiphilic non-ionic polyethylene glycol surfactant in an aqueous solution. The synthesized α-Fe 2 O 3 NPs were characterized by powder X-ray diffraction, field emission scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…Our result coincides with previously published results [ 38 , 39 ]. Additionally, the single and strong peak at 390 nm in the UV/Vis absorption spectrum confirmed that the SRLe -αFe 2 O 3 NPs had a spherical shape, similar to the findings of Kumar et al (2022) [ 40 ].…”
Section: Resultssupporting
confidence: 87%
“…Our result coincides with previously published results [ 38 , 39 ]. Additionally, the single and strong peak at 390 nm in the UV/Vis absorption spectrum confirmed that the SRLe -αFe 2 O 3 NPs had a spherical shape, similar to the findings of Kumar et al (2022) [ 40 ].…”
Section: Resultssupporting
confidence: 87%